Fenomena perokok wanita di wilayah kerja Puskesmas Tes, Kabuapten Lebong, Provinsi Bengkulu - Tri Addya Karini; Retna Siwi Padmawati (Berita Kedokteran Masyarakat (BKM), 2018)
Unique social features of female smokers in Lebong district of Bengkulu IndonesiaPurposeThis study aimed to determine the cause and process of women’s smoking behavior.MethodThis research was a phenomenological study involving 15 women who smoke and live in Tes village, Lebong District of Bengkulu. Data collection was conducted through in-depth interviews and participant observation. The triangulation of data was reached through in-depth interviews on two public health center staff, and four husbands of the participants.ResultsResults showed that imitating friends, having smoking mothers, financial independency, increased sensitivity and desire for cigarette smoke smell when pregnant were the reasons women wanted to smoke. Also, they enjoy cigarette smoking after meals and smoked as part of their culture (smoke on the day received salary and celebrations day “uleak”). If they were not smoking they got headaches, bitter mouth and tongue felt thick, and felt support from husbands towards smoking behavior. The study also found that there was not any education about the impacts of smoking.ConclusionIt is indispensable to do health education about the negative impacts of smoking on health for women which requires a special program to help women smokers to stop smoking and prevent non-smoking women from starting smoking, such as quit smoking counseling services.